2016
DOI: 10.1039/c5fo01536g
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity, proximate, mineral and volatile profiles along the flowering stages of Opuntia microdasys (Lehm.): defining potential applications

Abstract: Opuntia spp. flowers have been traditionally used for medical purposes, mostly because of their diversity in bioactive molecules with health promoting properties. The proximate, mineral and volatile compound profiles, together with the cytotoxic and antimicrobial properties were characterized in O. microdasys flowers at different maturity stages, revealing several statistically significant differences. O. microdasys stood out mainly for its high contents of dietary fiber, potassium and camphor, and its high ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Camphor was also the major compound in the fruit skins of O. macrorhiza (39%), which also showed significant percentages of nonanal (6.9%), cis-linalool oxide (6.5%), phenylethyl alcohol (6.5%), and translinalool oxide (6.3%). The predominance of camphor is in agreement with the volatile profiles that were previously characterized in different O. microdasys flowering stages (Chahdoura et al, 2016). This compound was previously reported for its biological properties and industrial applications, particularly in medical products (Santos & Cabot, 2015).…”
Section: Aroma Volatilessupporting
confidence: 90%
See 3 more Smart Citations
“…Camphor was also the major compound in the fruit skins of O. macrorhiza (39%), which also showed significant percentages of nonanal (6.9%), cis-linalool oxide (6.5%), phenylethyl alcohol (6.5%), and translinalool oxide (6.3%). The predominance of camphor is in agreement with the volatile profiles that were previously characterized in different O. microdasys flowering stages (Chahdoura et al, 2016). This compound was previously reported for its biological properties and industrial applications, particularly in medical products (Santos & Cabot, 2015).…”
Section: Aroma Volatilessupporting
confidence: 90%
“…The second and third most abundant organic acids in Opuntia skins were malic and oxalic acid, both detected in quantities around 1 g/100 g dw. In comparison to other botanical parts, fruit skins contain higher levels of organic acids than cladodes (Chahdoura et al, 2014a) and flowers (Chahdoura et al, 2016), which, nonetheless, have higher quantities than seeds (Chahdoura et al, 2015a). As far as we know, there are no reports describing the organic acids composition in the pulps and skins of the Opuntia species studied herein; however, some previous works reporting the chemical characterization of O. joconostle, O. matudae (Morales et al, 2012), O. ficus-indica, O. lindheimeri, O. streptacantha and O. stricta var.…”
Section: Organic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fungicidal power of OE against T. viride presented 3-fold lower concentrations (higher potential) than the fungicidal power displayed by bifonazole. Chahdoura et al (2016), tested the antimicrobial activity from Opuntia microdasys flowers and reported lower effects on their samples compared to OS, OG and OE extracts. Polyphenols and other biofunctional molecules, such as betalains, have shown the capacity to induce cellular damage in pathogenical microorganisms (Azeredo, 2009;Sansano, Rivas, PinaPérez, Martinez, & Rodrigo, 2017).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%